Geomatic Techniques Applied to the Dynamic Study (2001-2019) of the Rock Glacier in the Veleta Cirque (Sierra Nevada, Spain) - Sanjosé Blasco, José Juan de; Atkinson Gordo, Alan; Sánchez Fernández, Manuel; Gómez Ortiz, Antonio; Salvà i Catarineu, Montse; Salvador Franch, Ferran (Land, 2022)
During the Little Ice Age (LIA), Corral del Veleta (Sierra Nevada) housed a small glacier of which relict glacial ice and permafrost still remain under packets of ice blocks. Currently, it is considered the southernmost rock glacier in Europe. The analysis and results of monitoring carried out on this rock glacier reveal it to be in an accelerated process of immobilization and that the relict glacial ice blocks and permafrost on which it lies are in a continual process of degradation. The rock glacier was monitored from 2001 to 2019 using diverse geomatic techniques, to which geophysical and thermal techniques were added. The results obtained during the observation period shed light on the dynamic of the rock glacier (morpho-topographic movements and deformations) as well as the physical state of the underlying frozen bodies (volumetric reduction and spatial distribution). The changes observed are related to variations in the dominant high-mountain climate of Sierra Nevada, particularly since the end of the 20th century, the general tendencies of which are increasing temperatures, decreasing annual snowfall, and a shorter duration of snow on the ground.